2016
DOI: 10.1002/mnfr.201500613
|View full text |Cite
|
Sign up to set email alerts
|

A click chemistry approach identifies target proteins of xanthohumol

Abstract: We find support for the notion that XN modulates multiple pathways and processes by covalent modification of proteins with reactive cysteines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…419422 For the chalcone’s target identification, the design of the chalcone probes adopts one of the above strategies or a combination of them to obtain a multifunctional probe to identify their targets successfully. 25,101,289,374,423 For more information on the development of small-molecule probes, several recent reviews are available 374,399…”
Section: Target Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…419422 For the chalcone’s target identification, the design of the chalcone probes adopts one of the above strategies or a combination of them to obtain a multifunctional probe to identify their targets successfully. 25,101,289,374,423 For more information on the development of small-molecule probes, several recent reviews are available 374,399…”
Section: Target Identificationmentioning
confidence: 99%
“…289 Structurally, xanthohumol (Table 1, entry 17) is very similar to 4hydroxyderricin ( 142 ). Interestingly, this compound has attracted much attention due to its potential as a cancer chemopreventive agent.…”
Section: Target Identificationmentioning
confidence: 99%
“…Interestingly, the authors recorded that both the hydrogenation of 2 and Nrf2-knockdown in PC12 cells abolished its neuroprotective effect, indicating that the α,β-unsaturated ketone structure in 2 and the activation of Nrf2 are key determinants for the neuroprotection of 2 . More recently, Brodziak-Jarosz et al confirmed the ability of 2 to form a covalent bond with the sensor protein Keap1, an event that triggers Nrf2 activation, using a click chemistry approach and AREc32 cells [ 27 ]. They showed a weaker electrophilicity for 2 , suggesting its more selective interaction with the most nucleophilic thiols.…”
Section: Targeting the Nrf2 Pathway By Natural Chalconesmentioning
confidence: 99%
“…Further studies will be necessary to dissect the underlying molecular mode of action. Due to its electrophilic nature, 1 directly affects several cellular targets and signaling pathways 29 and modulates activity of kinases, such as Akt and AMPK, and of transcription factors, such as Nrf2, NF-kB, or STAT3. 19 , 30 , 31 All those signaling molecules may conceivably contribute to the reduced neointima formation.…”
mentioning
confidence: 99%